A review of climate change in South East Asian Countries and human health: Impacts, vulnerability, adaptation, and mitigation - Gamage, Anuji Upekshika; Pearson, Dess; Hanna, Fahad (South East Asia Journal of Public Health, 2017)
Climate Change (CC) is one of the most significant global environmental challenges humanity has faced. The most dominant causative factors due to human activity are emissions of greenhouse-gasses (GHG) from the combustion of fossil fuels and deforestation of natural rain forests. Although CC has a global impact, developing countries in the South East Asian Region (SEAR) would be more vulnerable to the effects as growth, development, poverty and health of these countries will be severely affected. The key ill-effects include increasing global average temperatures, the rise in sea levels, changes in eco-systems, and adverse impacts on human health. Rising sea levels threatens coastal cities; changes to the monsoon rainfall and a significant reduction in agricultural output are among some of the climate risks these countries will have to face. CC would compromise the essential prerequisites for good health; safe water, secure shelter, and food security and aggravate health risk through emerging and re-emerging diseases and spread of infectious diseases. Health-focused investments in climate actions remain weak and countries should focus on implementing health systems, while targeting for universal health coverage. The growth rate for Asian economies has risen over the past decade and this has led to steady emission increase. India and Indonesia are amongst the top ten emitters while others remain small emitters. Efforts are needed to limit the temperature increase to minimize adverse effects, which will require deep de-carbonization by both developed and developing countries, through an integrated portfolio of mitigation and adaptive strategies, which will be abide by UNFCCC common but differentiated approach. South East Asia Journal of Public Health Vol.6(2) 2016: 3-10